2013
DOI: 10.1088/1475-7516/2013/05/022
|View full text |Cite
|
Sign up to set email alerts
|

On the spin bias of satellite galaxies in the local group-like environment

Abstract: Abstract. We utilize the Millennium-II simulation databases to study the spin bias of dark subhalos in the Local Group-like systems which have two prominent satellites with comparable masses. Selecting the group-size halos with total mass similar to that of the Local Group (LG) from the friends-of-friends halo catalog and locating their subhalos from the substructure catalog, we determine the most massive (main) and second to the most massive (submain) ones among the subhalos hosted by each selected halo. When… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…The left panel shows the specific angular momentum as a function of the halo mass. Compared to halos without neighbors, those with neighbors have, on average, a slightly higher j core , and it is consistent with the previous findings (e.g., Lee & Lemson 2013;Johnson et al 2019). Although the increase in j core is statistically significant, the difference between the two subsamples is quite small.…”
Section: Linking Soa To Interaction With Neighborssupporting
confidence: 90%
“…The left panel shows the specific angular momentum as a function of the halo mass. Compared to halos without neighbors, those with neighbors have, on average, a slightly higher j core , and it is consistent with the previous findings (e.g., Lee & Lemson 2013;Johnson et al 2019). Although the increase in j core is statistically significant, the difference between the two subsamples is quite small.…”
Section: Linking Soa To Interaction With Neighborssupporting
confidence: 90%
“…The mass resolution of BoxA (2.6 × 10 5 h −1 M per particle) is very close to that of the Aquarius-A simulation at level 4 (Springel et al 2008) which had a particle mass of 2.7 × 10 5 h −1 M in the high resolution region. This is roughly three times better mass resolution than the Millennium-II simulation (m p = 6.9 × 10 6 h −1 M ) used by Lee & Lemson (2013). The cosmology was chosen to be the same as in the Aquarius simulation, i.e.…”
Section: Simulation Datamentioning
confidence: 99%
“…Due to a lack of resolution in previous generations of large cosmological simulations, subhalo spins have not been thoroughly investigated so far, despite their application within current semi-analytic models (Guo et al 2011). Initial work by Lee & Lemson (2013) analyzed the spins of the two most massive substructures of Local Group like systems in the Millennium-II simulation (Boylan-Kolchin et al 2009) and revealed possible consequences for the application of subhalo spins to near-field cosmology. Onions et al (2013) investigated the spin distribution of subhaloes in two high resolution simulations of a Milky Waylike halo (the Aquarius simulation (Springel et al 2008) and the GHALO simulation (Stadel et al 2009)) analyzed by a variety of subhalo finders.…”
Section: Introductionmentioning
confidence: 99%
“…Their mass resolution is equivalent to the resolution of the Aquarius project simulations at level 5 and level 4, respectively (Springel et al 2008). The mass resolution of the Aquarius simulation at level 5 is roughly three times higher than that of the Millennium-II simulation (mp = 6.9 × 10 6 h −1 M ) used by Lee & Lemson (2013). The cosmology was chosen to be the same as in the Aquarius simulation, i.e.…”
Section: Convergence Studymentioning
confidence: 99%